2023
DOI: 10.1002/aur.2900
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of item bias in a national flourishing measure for autistic youth

Abstract: Flourishing is a positive health indicator that aligns with strengths‐based perspectives and measures within autism research. Flourishing indicators were recently included in the National Survey of Children's Health (NSCH) and have been used to evidence disparities in flourishing experienced by autistic children compared to non‐autistic peers. Yet, little has been done to examine the utility of standard flourishing items for this population. This study examined the NSCH caregiver‐reported flourishing items for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…However, additional research is needed to identify if this is due to internalised ableism, lack of accessible measures, and/or measures that are not inclusive of strengths unique to adults with intellectual disability. For instance, a recent study using data from the National Survey of Children's Health, found more than half of the items from a new flourishing metric had measurement bias when used among children with autism (Ross et al, 2023). Revisions of the VIA Inventory of Strengths to enhance cognitive accessibility may provide people with intellectual disability an opportunity to report their strengths and also enhance access to individuals with other types of cognitive impairments.…”
Section: Discussionmentioning
confidence: 99%
“…However, additional research is needed to identify if this is due to internalised ableism, lack of accessible measures, and/or measures that are not inclusive of strengths unique to adults with intellectual disability. For instance, a recent study using data from the National Survey of Children's Health, found more than half of the items from a new flourishing metric had measurement bias when used among children with autism (Ross et al, 2023). Revisions of the VIA Inventory of Strengths to enhance cognitive accessibility may provide people with intellectual disability an opportunity to report their strengths and also enhance access to individuals with other types of cognitive impairments.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that understanding caregiver perceptions of emotional support and community and cultural assets is valuable, especially in the context of valuing the lived experiences of families and their perceptions of the systems in which they live rather than what the system believes to be providing. While some have proposed the child flourishing measure can be biased for certain populations, like caregivers of children with autism, 63 it was developed by experts for the broader child population with consideration given to optimizing the validity of caregiver report. Third, we used publicly available data, so metro and nonmetro data are available only in states where there are no concerns over the reidentification of respondents.…”
Section: Discussionmentioning
confidence: 99%
“…However, differences in neuropsychological processing can impact the way that individuals process information (see Franzen, 2000), and thus there may be different relations between variables for groups with atypical neuropsychological function, such as those on the autism spectrum. For example, recent research has shown that measures designed and normed with allistic individuals may not have equal utility when used with those on the autism spectrum (Ross et al, 2023). Moreover, cognitive processes that correlate in allistic individuals may show distinct and diverse patterns from those with conditions that impact the way information is processed (Delis, 2001).…”
Section: Ei In Autismmentioning
confidence: 99%